Notch2/3-DLL4 interaction in urothelial cancer cell lines supports a tumorigenic role of Notch signaling pathways in bladder carcinoma - Chuan Zhang; Annett Weimann; Jens-Uwe Stolzenburg; Jochen Neuhaus; Mandy Berndt-Paetz (PLoS ONE, 2025)
Introduction The Notch pathway plays an important role in many aspects of cancer biology and acts in a dichotomous way in bladder cancer. The mechanisms behind this behavior are still elusive. Here, we analyzed DLL4 and Notch receptor expression, interaction and downstream signaling in human bladder cancer cells. Materials and methods The expression levels of Notch pathway components (Notch1-4, DLL4, HES1, HEY1) were assessed in papillary (G1: RT-4) and non-papillary bladder cancer cell lines (G2-G4: RT-112, 647-V, T-24, KU-19-19, CAL-29) by qRT-PCR and immunofluorescence. Expression data were validated by analyzing data from open-source databases (CCLE; TCGA). The endogeneous interactions of Notch2/Notch3 receptors and the ligand DLL4 were studied by in situ proximity ligation assay. Activation of canonical Notch signaling was evaluated by stimulation with recombinant DLL4 protein. Results All Notch targets were expressed, with Notch2 and Notch3 showing the highest expression levels. Endogeneous interactions between Notch2/3 and DLL4 were detected in all BCa cell lines. Amounts of Notch2/3-DLL4 complexes were high in RT-112 and CAL-29, while RT-4/647-V showed moderate and T-24, KU-19-19 low abundance. Proportion of (peri-) nuclear interaction complexes correlated negatively with Notch downstream targets. DLL4 stimulation resulted in canonical Notch pathway activation and increased tumor cell viability and proliferation in RT-4, 647-V, T-24 and KU-19-19 cells. Discussion The Notch signaling pathway can discriminate between different receptors and may play an essential role in the progression of bladder carcinoma. We demonstrated for the first time direct interactions between DLL4 and Notch2/3 associated to activation of canonical downstream Notch signaling and increased tumor cell behavior in human bladder cancer cells. Our data support the view that the Notch2/3-DLL4 axis plays an oncogenic role in bladder cancer. Further analyses of Notch signaling in bladder cancer can promote the development of tailored anti-DLL4/Notch bladder cancer therapies in the future.